- Today we reconsidered the linear equation & the general form of a linear equation is y = mx + c
- where by the m refers to the GRADIENT
- where c is the Y-INTERCEPT (or the value of y when x = 0)
- m is POSITIVE when as x increases, y also increases
- m is NEGATIVE when as x increases, y will decrease
- m is ZERO when as x changes, y is constant (HORIZONTAL LINE)
- m is undefined when x is constant and y changes (VERTICAL LINE)
- X-INTERCEPT would be equal to -c / m ... (or the value of x when y = 0)

NOTE - c (or the constant in all the equation) is always the y-intercept, even for equations such as y = ax^2 + bx + c ...

Why do you think this is so? (HINT - look at point (3) above)

Prove point (8) for yourself ...

For y intercept let x be equal to 0.

ReplyDeleteTherefore a(0)^2+b(0)+c(0)=C

Therefore,y=mx+c= (0,C)

For y=mx+c

ReplyDeleteFor the x intercept

y=0

0=mx+c

mx=-c

x=-c/m